Aggregation-induced emission–based highly selective 'turn-off' fluorogenic chemosensor for robust quantification of explosive picric acid in aqueous and solid states. (December 2019) - Shyamal, M.; Das, D.; Giri, P.K.; Maity, S.; Misra, A.
Abstract: An exclusive fluorescent probe, N, N′-di-[2-hydroxy-3-methoxy-benzylidene]-benzene-1, 4-diamine (DBA), has been well designed and synthesized. Intriguingly, it displayed attractive aggregation-induced emission (AIE) phenomenon in aqueous media. Based on its interesting AIE characteristic, the fluorescent hydrosol has been used as a sensor with swift sensitivity and excellent selectivity toward nitro-explosive picric acid (PA) and the limit of detection (LOD) as low as 72 nM and 2.3 ng in aqueous and solid states, respectively. The recognition event occurs absolutely within 10 s after the addition of PA, demonstrating a promising 'zero-wait' recognition method. Fluorescent paper strips were prepared for instant trace recognition of PA by naked eye in solid state, making the protocol fast, inexpensive, and practical for on-site solid-state detection. Graphical abstract: Image 1 Highlights: A shrewdly designed novel aggregation-induced emission based fluorescent chemosensor DBA is synthesized. It produces distinct fluorescent crystalline microstructures from 0-D to 1-D. It furnishes brilliant orange colour fluorescent nanoaggregates in mixed aqueous media. The nanoaggregates exhibited excellent selectivity and swift sensitivity toward explosive picric acid (PA) at ppb level. PA was detected by the nanoaggregates-coated TLC strips in 'naked eye'.